2018
DOI: 10.4269/ajtmh.18-0356
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Polymerase Chain Reaction for Diagnosis of Soil-Transmitted Helminth Infections: A Comparison with a Flotation-Based Technique and an Investigation of Variability in DNA Detection

Abstract: Appropriate diagnostic techniques are crucial to global soil-transmitted helminth (STH) control efforts. The recommended Kato-Katz method has low sensitivity in low-transmission settings. Quantitative polymerase chain reaction (qPCR) is a highly sensitive alternative diagnostic option. However, little is known about the variability in qPCR results, and there are few published comparisons between qPCR and other microscopy-based techniques such as sodium nitrate flotation (SNF). Using 865 stool samples collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Of all diagnostic methods, qPCR had the highest clinical sensitivity for all three STHs. This finding is largely in line with previous studies that compared the qPCR with microscopic methods (direct smear, wet preparation, Kato-Katz (single and duplicate on single or multiple stool samples over consecutive days), McMaster and/or sodium nitrate flotation [2436]). However, in contrast to our findings and those listed above, Knopp and coworkers (2014) found a lesser clinical sensitivity of qPCR (73.6%) compared to microscopic methods (83.3% by means of FLOTAC and 75.0% by means of Kato-Katz) for the detection of hookworm in Tanzania, although not regarded as significant [37].…”
Section: Discussionsupporting
confidence: 90%
“…Of all diagnostic methods, qPCR had the highest clinical sensitivity for all three STHs. This finding is largely in line with previous studies that compared the qPCR with microscopic methods (direct smear, wet preparation, Kato-Katz (single and duplicate on single or multiple stool samples over consecutive days), McMaster and/or sodium nitrate flotation [2436]). However, in contrast to our findings and those listed above, Knopp and coworkers (2014) found a lesser clinical sensitivity of qPCR (73.6%) compared to microscopic methods (83.3% by means of FLOTAC and 75.0% by means of Kato-Katz) for the detection of hookworm in Tanzania, although not regarded as significant [37].…”
Section: Discussionsupporting
confidence: 90%
“…Modeling has shown that the threshold must be based on true prevalence (Truscott et al, 2017; Ásbjörnsdóttir et al, 2017), which can only be accurately estimated with highly sensitive and species-specific diagnostics. Improved diagnostics are crucial to meet this need (Kongs et al, 2001; Andersen et al, 2013; Clarke et al, 2018; Hidalgo et al, 2018). Post-MDA surveillance is also necessary.…”
Section: Resultsmentioning
confidence: 99%
“…This trial will provide robust evidence regarding the differential impact of school-based and community-wide deworming on STH infections among school-age children, who are at high risk of STH-associated morbidity. The use of qPCR to diagnose and quantify infections among the study population will not only allow for a more accurate determination of disease prevalence and intensity before and after deworming [30, 39], but will also contribute to the evidence base for using more sensitive diagnostic techniques to monitor the impact of deworming. This is an increasingly important consideration as global deworming efforts continue and STH prevalence and intensity declines to that undetectable by microscopy in many regions [37, 40].…”
Section: Discussionmentioning
confidence: 99%